Key knowledge gaps for One Health approach to mitigate nanoplastic risks - Dang, Fei; Wang, Qingyu; Huang, Yingnan; Wang, Yujun; Xing, Baoshan (Eco-Environment & Health, 2022)
There are increasing concerns over the threat of nanoplastics to environmental and human health. However, multidisciplinary barriers persist between the communities assessing the risks to environmental and human health. As a result, the hazards and risks of nanoplastics remain uncertain. Here, we identify key knowledge gaps by evaluating the exposure of nanoplastics in the environment, assessing their bio-nano interactions, and examining their potential risks to humans and the environment. We suggest considering nanoplastics a complex and dynamic mixture of polymers, additives, and contaminants, with interconnected risks to environmental and human health. We call for comprehensive integration of One Health approach to produce robust multidisciplinary evidence to nanoplastics threats at the planetary level. Although there are many challenges, this holistic approach incorporates the relevance of environmental exposure and multi-sectoral responses, which provide the opportunity to identify the risk mitigation strategies of nanoplastics to build resilient health systems. [Display omitted] •Nanoplastic is a complex and dynamic mixture of polymer, additive, and contaminant.•Knowledge gaps persist in exposure, bio–nano interactions, and potential risks.•A one health approach is critical to achieve environmental and human health.•Environmental exposure, multi-responses, and mitigation strategies are integrated.